Peran Subsektor Peternakan terhadap Perekonomian Lampung Tahun 2020-2023 - Asek, Ambo; Suradi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
The livestock subsector in Lampung Province is the subsector with the largest economic growth compared to other subsectors. The average economic growth of the livestock subsector is 6.2%, and it is the largest compared to other subsectors. This indicates that this subsector plays a crucial role in Lampung's economy. The purpose of this research is to analyze the livestock subsector's role in the Economy of Lampung Province during the 2020–2023 period. This study employs a quantitative descriptive method using a secondary data analysis approach. The research location is focused on Lampung Province. The secondary data utilized are the value of the Gross Regional Domestic Product (GRDP) for all sectors and the GRDP of the livestock subsector in Lampung Province, presented at constant prices (ADHK/Constant Price Basis). The data were obtained from the Central Bureau of Statistics (BPS) and the Provincial Livestock and Animal Health Office of Lampung. Data analysis was performed using the Location Quotient (LQ) method. The research findings indicate that the livestock subsector constitutes a base and leading sector in the economic structure of Lampung Province. Keywords: livestock subsector, Location Quotient (LQ), base sector, GRDP, Lampung province